Trade in Health Services : What’s in it for Developing Countries? - Cattaneo, Olivier (2012)
This study summarizes the existing knowledge and relevant abstracts and case-studies on the design of health and/or trade reforms and policies. The study aims to contribute to the understanding of the potential benefits and risks - and ways to maximize the former and minimize the latter - of trade in the health sector. It is designed for non-trade (health) experts to understand how trade can help to improve health systems and access to health services, and for trade specialists to understand the specific characteristics of the health sector.